A distinctive stellate species of the genus Actinocyclus (Bacillariophyta) from Oligocene sediments in the central Pacific Ocean and its morphological significance. Issue 2 (4th March 2022) - Wu, Cong; Williams, David M.; Peng, Zhiyuan; Chen, Chixin
ABSTRACT: Actinocyclus asteriscus, a notable species with star-like hyaline rays on the valves discovered in Oligocene sediments from the central Pacific Ocean, has been examined in detail with light and scanning electron microscopy. Its unique appearance with complete hyaline rays helps the initial identification of diatom valves in the microscope. The taxonomic relationships between A. asteriscus and species belonging to six well-defined groups of Actinocyclus species are discussed with a special focus on the hyaline structure. On the basis of the geological time range and ecological habitat of selected Actinocyclus species, we hypothesize that A. asteriscus possesses the primary type of hyaline structure and that this feature subsequently degenerated in other species of the genus. In addition, quantitative data on the relationship between valve diameter and number of hyaline rays and the areolae density are discussed to address the divergence in intraspecific morphological features.